Effect of different extraction methods on vitamin B12 from edible green seaweed, Ulva lactuca by 2-Level Factorial Design - Ruslan, Fatin Shazwani; Darnis, Deny Susanti; Mohammad Noor, Normawaty; Bakhtiar, M. Taher; Aminudin, Nurul Iman (2021)
Ulva lactuca has been known for its valuable biological properties such as antioxidant and antiviral due to the presence of several bioactive compounds like vitamins, polysaccharides, and lipids. In the present study, different extraction procedures of vitamin B12 were compared. Four types of dried U. lactuca (oven-dried, sun-dried, air-dried, freeze-dried) were subjected to three different extraction methods each (boiling, orbital shaking, and ultrasonic-assisted extraction (UAE)). Also, the effect of solvent:solvent (MeOH:H2O), solute:solvent ratio, and pH on the total vitamin B12 content were screened and statistically analysed using 2-Level Factorial design from RSM. The retention time (RT) from HPLC of all crude extracts were corresponded with the RT of standard cyanocobalamin (CN-Cbl) at 1.9 minutes. The extraction of CN-Cbl by orbital shaking gave insignificant (p > 0.05) result on the yield of CN-Cbl, compared to the boiling and UAE methods when oven-dried U. lactuca were extracted (p < 0.05). The highest concentration of CN-Cbl (0.0236 mg/mL) was recorded when extracted by UAE method at parameters of 25:75 % MeOH:H2O, pH 3, 3 g: 60 mL solute:solvent ratio. Statistically, the concentration of CN-Cbl increased significantly (p < 0.05) with decreasing MeOH:H2O, solute:solvent ratios and pH when U. lactuca was subjected to oven-dried drying method, and extracted using UAE method. Hence, these factors may be further optimised in the future research to extract a better yield of CN-Cbl.